Article RETRACTED due to manipulation by the authors The effect of training on flexibility: a case study of athletes and non-athletes - Nuridin Widya Pranoto; Heru Andika; Yovhandra Ockta; Kamal Firdaus; Nofri Hendri; Fiky Zarya; Vlad Adrian Geantă; Aydın Karaçam; varhatun fauziah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background and Objectives: Flexibility is one of the main components of physical fitness that is important in improving athletic performance and general health. This study aims to evaluate the effect of training on flexibility and compare the effectiveness of training in athletes and non-athletes. Methodology:This study used an observational case study design involving 460 participants aged 18-20 years who were divided into two groups, namely athletes and non-athletes. The athlete group consisted of individuals who were routinely involved in intensive physical activity, while non-athletes did not have a structured physical exercise routine. Flexibility tests were conducted using the sit-and-reach method before and after the exercise program. Data were analyzed using paired t-tests and unpaired t-tests to evaluate differences in flexibility improvement between the two groups. Results: Athletes, who regularly engage in intensive physical activity, showed a more significant increase in flexibility than non-athletes. The athlete group had a higher average flexibility, with a statistically significant difference, with an average increase of 26 cm in athletes and 15 cm in non-athletes (p < 0.05). The difference in flexibility improvement between the two groups was also statistically significant, with an average difference of 11 cm (p < 0.05). Conclusion: This study confirms that regular physical exercise significantly improves flexibility, especially in athletes. The athlete group showed a better response to the exercise program compared to non-athletes, which emphasizes the importance of structured exercise in maintaining and improving flexibility. These findings can provide insights for coaches, physiotherapists, and health professionals in designing effective exercise programs for various population groups.